2023
DOI: 10.1002/dad2.12509
|View full text |Cite
|
Sign up to set email alerts
|

Bilingual neurocognitive resiliency, vulnerability, and Alzheimer's disease biomarker correlates in Latino older adults enrolled in the Health and Aging Brain Study ‐ Health Disparities (HABS‐HD)

Stephanie M. Grasso,
Alexandra L. Clark,
Melissa Petersen
et al.

Abstract: INTRODUCTIONThe effects of bilingualism on neuropsychological test performance in bilinguals with and without cognitive impairment are not well‐understood and are relatively limited by small sample sizes of Latinos.METHODSUsing analysis of covariance (ANCOVA), we explored patterns of cognitive performance and impairment across a large sample of community‐dwelling bilingual and monolingual Latino older adults with (n = 180) and without (n = 643) mild cognitive impairment (MCI) enrolled in HABS‐HD.RESULTSBilingu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 77 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…There is evidence suggesting that bilingualism may help individuals maintain cognition against the consequences of brain aging and consequential dementia neuropathology (Abutalebi et al, 2014;Anderson et al, 2018Anderson et al, , 2021Berkes et al, 2021;Costa & Sebastián-Gallés, 2014;Gallo et al, 2020;Gold et al, 2013;Grasso et al, 2023;Li et al, 2017;Olsen et al, 2015;Schroeder & Marian, 2012). Research has shown that bilingual older adults who progress to impairment reach the clinical threshold for diagnosis of Alzheimer's Disease approximately 4.5 years later than comparable monolinguals (Craik et al, 2010;Gollan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence suggesting that bilingualism may help individuals maintain cognition against the consequences of brain aging and consequential dementia neuropathology (Abutalebi et al, 2014;Anderson et al, 2018Anderson et al, , 2021Berkes et al, 2021;Costa & Sebastián-Gallés, 2014;Gallo et al, 2020;Gold et al, 2013;Grasso et al, 2023;Li et al, 2017;Olsen et al, 2015;Schroeder & Marian, 2012). Research has shown that bilingual older adults who progress to impairment reach the clinical threshold for diagnosis of Alzheimer's Disease approximately 4.5 years later than comparable monolinguals (Craik et al, 2010;Gollan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%